Mesoporous Carbon Nanocube Architecture for High-Performance Lithium-Oxygen Batteries - Sun, Bing; Chen, Shuangqiang; Liu, Hao; Wang, Guoxiu (Advanced functional materials, 2015)
One of the major challenges to develop high‐performance lithium–oxygen (Li–O2) battery is to find effective cathode catalysts and design porous architecture for the promotion of both oxygen reduction reactions and oxygen evolution reactions. Herein, the synthesis of mesoporous carbon nanocubes as a new cathode nanoarchitecture for Li–O2 batteries is reported. The oxygen electrodes made of mesoporous carbon nanocubes contain numerously hierarchical mesopores and macropores, which can facilitate oxygen diffusion and electrolyte impregnation throughout the electrode, and provide sufficient spaces to accommodate insoluble discharge products. When they are applied as cathode catalysts, the Li–O2 cells deliver discharge capacities of 26 100 mA h g−1 at 200 mA g−1, which is much higher than that of commercial carbon black catalysts. Furthermore, the mesoporous nanocube architecture can also serve as a conductive host structure for other highly efficient catalysts. For instance, the Ru functionalized mesoporous carbon nanocubes show excellent catalytic activities toward oxygen evolution reactions. Li–O2 batteries with Ru functionalized mesoporous carbon nanocube catalysts demonstrate a high charge/discharge electrical energy efficiency of 86.2% at 200 mA g−1 under voltage limitation and a good cycling performance up to 120 cycles at 400 mA g−1 with the curtaining capacity of 1000 mA h g−1. Mesoporous carbon nanocubes (MCCs) are synthesized by a chemical vapor deposition method. Oxygen electrode made of MCCs contains a hierarchical porous structure, which can facilitate oxygen diffusion, electrolyte impregnation, and accommodation of discharge products during the charge and discharge processes.